2017
DOI: 10.3923/pjbs.2017.355.364
|View full text |Cite
|
Sign up to set email alerts
|

Zeatin and Thidiazuron Induced Embryogenic Calli From In Vitro Leaf and Stem of Jojoba (Simmondsia chinensis)

Abstract: Background and Objective: Jojoba is a promising industrial plant, which recommended with pharmaceutical benefits. The present study was conducted to stimulate embryogenic calli formation from jojoba using zeatin and thidiazuron (TDZ), as well as determination of the antioxidant activity of proliferated calli. Materials and Methods: For callus induction, leaf and stem explants derived from in vitro grown shootlets, were cultured on Murashige and Skoog (MS) medium with different combinations of 0.5 mg LG 1 benzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…On this medium, the percentage of callus induction was 80 and the morphogenic response of observed callus was light green in color with soft texture. Similar findings were reported by El-Ashry et al (2017). They reported that MS supplemented with 0.5 mg/l BA + 0.5 or 1 mg/l picloram was the best treatment to obtain friable calli from leaf explants of jojoba.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On this medium, the percentage of callus induction was 80 and the morphogenic response of observed callus was light green in color with soft texture. Similar findings were reported by El-Ashry et al (2017). They reported that MS supplemented with 0.5 mg/l BA + 0.5 or 1 mg/l picloram was the best treatment to obtain friable calli from leaf explants of jojoba.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, the development of an efficient callus proliferation system is a prerequisite for a number of biotechnological interventions for the improvement of jojoba, such as genetic transformation, production of useful metabolites in vitro, etc. In this context, callus induction of jojoba plant were reported using two different types of explants, i.e., immature zygotic embryos, leaf disks and stem explants (Gaber et al 2007, El-Ashry et al 2017. The present work aimed at developing an effective protocol for in vitro shoot buds multiplication and callus proliferation of jojoba.…”
Section: Introductionmentioning
confidence: 98%
“…However, they observed a significantly smaller number of shoots per explant (mean number of three shoots/explant) compared to our protocol, where the average number of newly formed buds on the zeatin-containing media was 6.00-11.00. The data in the literature confirm that the effect of zeatin on plant morphogenesis and shoot formation is highly dependent on its concentration [44]. As the data in the literature show that the combination of BAP (0.2 mg/L and 0.5 mg/L) with NAA (1 mg/L) has a positive effect on the morphological development and polyphenolic production of S. scardica in vitro cultures [30], we also studied the effect of the addition of BAP.…”
Section: Discussionsupporting
confidence: 52%
“…The increase in the concentration of TDZ at a high rate can result in a decrease of shoot regeneration and browning of callus, 46 and it maybe because of its stimulatory role on endogenous ethylene production 87 . The work of El‐Ashry et al 88 . suggested that embryogenic calli, which have originated from stem explants, showed the highest antioxidant activity with ether extracted at TDZ concentration of 1 mg L −1 .…”
Section: Factors Affecting the Efficiency Of Thidiazuron In Callus In...mentioning
confidence: 99%